113k views
1 vote
-3x^2+12x-8 in vertex form using the completing the square method! ASAP PLEASE WILL MARK U WHATEVER YOU WANT! WORK NEEDED

2 Answers

4 votes

Answer: y=−3(x−2)^2+4

Explanation:

f(x)=-3*x^2+12*x+-8

f(x)=-3*(x^2+-4*x+8/3) ( Factor out )

f(x)=-3*(x^2+-4*x+(-2)^2+-1*(-2)^2+8/3) ( Complete the square )

f(x)=-3*((x+-2)^2+-1*(-2)^2+8/3) ( Use the binomial formula )

f(x)=-3*((x+-2)^2+1*-4/3) ( simplify )

f(x)=-3*(x+-2)^2+4 ( expand )

0 votes

Answer:

-3x2 + 12x - 8

Explanation:

Equation at the end of step 1

((0 - 3x2) + 12x) - 8

STEP

2

:

STEP

3

:

Pulling out like terms

3.1 Pull out like factors :

-3x2 + 12x - 8 = -1 • (3x2 - 12x + 8)

Trying to factor by splitting the middle term

3.2 Factoring 3x2 - 12x + 8

The first term is, 3x2 its coefficient is 3 .

The middle term is, -12x its coefficient is -12 .

The last term, "the constant", is +8

Step-1 : Multiply the coefficient of the first term by the constant 3 • 8 = 24

Step-2 : Find two factors of 24 whose sum equals the coefficient of the middle term, which is -12 .

-24 + -1 = -25

-12 + -2 = -14

-8 + -3 = -11

-6 + -4 = -10

-4 + -6 = -10

-3 + -8 = -11

-2 + -12 = -14

-1 + -24 = -25

1 + 24 = 25

2 + 12 = 14

3 + 8 = 11

4 + 6 = 10

6 + 4 = 10

8 + 3 = 11

12 + 2 = 14

24 + 1 = 25

User Cvincent
by
4.6k points